Enhancement of chemical information management system through business process reengineering / Ahmad Zulhilmi Zamri - Zamri, Ahmad Zulhilmi (2012)
The aim of this research is to enhance the chemical distribution process which is one of sub module from the Laboratory Management Module of Chemical Information Management System (CMS). The objective of this research is to examine the existing system for enhancement, to design the existing chemical distribution process and to demonstrate the process of chemical distribution module. Indeed, this research focuses on the managing of the chemical laboratory of Mara University of Technology in particular of chemical distribution process from laboratory to laboratory and from inventory to laboratory. The main users of this system is the laboratory assistant who are responsible to manage the distribution chemical. To solve this problem, Business Process Reengineering (BPR) approach has been employed. BPR consist of three stages which are prepare for reengineering, map and analyze business process and design and implement reengineering process. The significance of this research includes helping laboratory assistant to manage the distribution of chemicals and to help lecturer request any chemicals to be used in a lab.